An Exploratory Study of Sukuk Utilisation for Transportation Infrastructure Development in Indonesia - Lamari, Fiona; Rarasati, Ayomi Dita; Evita, Meilia (Makara Journal of Technology, 2018)
Investment in infrastructure is one of the principal drivers of the growth of the economy. For that reason, the Indonesian government has proposed an investment budget in the railway and sea and air transport sectors over the next 10 years. In order to overcome the burden of direct outflows and for the future, a study was conducted to lay down the framework of Shariah-compliant payments for the development of infrastructure in Indonesia in the transport sector. This paper aims to explore the opportunity and implementation of sukuk utilisation to develop transportation infrastructure. Secondary data study and interviews were selected for the basic research method. This study presents the practice of sukuk implementation in transportation projects. Six transportation projects are also described to gain insight of the utilisation shariah-compliant financing scheme.